Establishment of ANEDr model for evaluating absorbed-nitrogen effects on wheat dry matter production - Jiao ZHAO; Hong-bin TAO; Shu-hua LIAO; Pu WANG (Journal of Integrative Agriculture, 2016)
Applying mathematic models to evaluate absorbed-N effects on dry matter production at different developmental stages would help determine proper nitrogen management according to crop demands and yield target. Two field trials were carried out for establishing absorbed-N effects on dry matter production (ANEDr) model, using uniform design in 2010–2011 and 2012–2013 winter wheat growing seasons in Hebei Province, China. Another field trial was carried out in 2010–2011 for model validation. Dry matter and N concentration in leaf and non-leaf organs were measured at setting, jointing, anthesis, and maturity. Theory of best linear unbiased prediction (BLUP) was applied to analyse the N effects of leaf and non-leaf organs on dry matter production. Within ANEDr model, four N-affected phases at each stage were concerned, leaf absorbed-N effect before this stage, non-leaf organ absorbed-N effect before this stage, leaf absorbed-N effect at this stage, and non-leaf organ absorbed-N effect at this stage. In addition, developmental processes, genotype characters and temperature were three factors that determine each N effect. It was demonstrated that ANEDr model can precisely quantify absorbed-N effects on dry matter production with high correlation coefficient (r=0.95). Comparing with other models, ANEDr model considered both leaf and non-leaf organs according to developmental processes of winter wheat, showed higher flexibility and simplicity, thus could be applied to different environments, cultivars and crops after parameter adjustment.